2022
DOI: 10.3390/ani12070853
|View full text |Cite
|
Sign up to set email alerts
|

Minimum Alveolar Concentration of Isoflurane in Rats Chronically Treated with the Synthetic Cannabinoid WIN 55,212-2

Abstract: The minimum alveolar concentration MAC of isoflurane was measured in rats chronically treated with WIN 55,212-2. Methods: The MAC of isoflurane was determined in 24 male rats from expiratory samples at time of tail clamping under the following conditions: without treatment MAC(ISO), in rats treated for 21 days with WIN 55,212-2 MAC(ISO + WIN55), and in rats 8 days after stopping treatment with WIN 55,212-2 (MACISO + WIN55 + 8D). Results: The MAC(ISO) was 1.32 ± 0.06. In the MAC(ISO + WIN55) group, the MAC incr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
4
0
0
Order By: Relevance
“…The minimum alveolar concentration was measured as 1.32 ± 0.06 in the MAC(ISO) group and 1.69 ± 0.09 in the MAC(ISO+WIN55) group. These values coincide with those previously reported in (20). MAC was measured as 0.97 ± 0.02 in the MAC(ISO+MOR) group (26% less than the control group MAC(ISO)), 1.55 ± 0.08 in the MAC(ISO+WIN55+MOR) group (8% less than the MAC(ISO+WIN55) group), 0.68 ± 0.10 in the MAC(ISO+DEX) group (48% less than the control group MAC(ISO)), and 0.67 ± 0.08 in the MAC(ISO+WIN55+DEX) group (60% less than the MAC(ISO+WIN55) group) (See table 1, 2).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The minimum alveolar concentration was measured as 1.32 ± 0.06 in the MAC(ISO) group and 1.69 ± 0.09 in the MAC(ISO+WIN55) group. These values coincide with those previously reported in (20). MAC was measured as 0.97 ± 0.02 in the MAC(ISO+MOR) group (26% less than the control group MAC(ISO)), 1.55 ± 0.08 in the MAC(ISO+WIN55+MOR) group (8% less than the MAC(ISO+WIN55) group), 0.68 ± 0.10 in the MAC(ISO+DEX) group (48% less than the control group MAC(ISO)), and 0.67 ± 0.08 in the MAC(ISO+WIN55+DEX) group (60% less than the MAC(ISO+WIN55) group) (See table 1, 2).…”
Section: Resultssupporting
confidence: 93%
“…In this study, we observed that the repeated administration of the synthetic cannabinoid WIN 55,212-2 55 for 21 days increases the MAC of isoflurane. This result coincides with those previously reported in (20). According to the obtained results, morphine decreases the MAC of isoflurane by 26%, which coincides with results previously reported in the literature (16).…”
Section: Discussionsupporting
confidence: 93%
“…MAC (ISO) was 1.32 ± 0.06 and MAC (ISO + CANN) was 1.69 ± 0.09, in agreement with the results of previously published studies [ 21 ]. MAC (ISO + MOR) was 0.97 ± 0.02 (26% less than MAC (ISO) ).…”
Section: Resultssupporting
confidence: 92%
“…In this study, we observed that the repeated administration of a cannabinoid for 21 days augmented the minimum alveolar concentration of isoflurane. This result coincides with those previously reported [21], in which the increase in the minimum alveolar concentration of isoflurane was attributed to an increase in norepinephrine efflux (previously…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation